Clinical outcome of malaria cases and malarial acute kidney injury in Hospital Serdang. A single center experience from 2007 till 2016 - Thevandran, Kalaiselvam; Premila, A. A.; Lim, Christopher Thiam Seong; Goh, Bak Leong (Elsevier, 2017)
Introduction: Malaria, a common health problem in certain parts of the world, has a considerable morbidity and mortality. This study reports its clinical outcome as well as Acute Kidney Injury (AKI) outcome from a single tertiary hospital from 2007 till 2016. Methods: All registered malaria cases with positive Plasmodium (P) sp from blood smears patients from hospital infection control database, were included in this study. History, examination, and baseline investigations recorded. Clinical outcome and AKI during stay was ana-lysed using SPSS version 23, with Pearson Chi Square test. Statistical significance taken when p value<0.05. Results: Seventy six malaria patients were recorded from January 2007 till December 2016 in Hospital Serdang. Majority were male (90.8%), young (31.9±10 years), from Selangor (89.5%) and foreigners (74%). Foreigners were mainly (75%) from Africa (27%), Pakistan (27%) and Indonesia (21%). P. Vivax species recoreded highest (55.3%), followed by P. Falciparum (28.9%), P.Knowlesi (7.9%), P. Malariae (6.6%), and P.Ovale (1.3%). All patients had fever, gastrointestinal symptoms (65.8%), central nervous symptom (43.4%), hepatosplenomegaly (25%) andoliguria (5.3%). Baseline laboratorary investigations showed Hemoglobin 13.1 ±2.1g/dL, Platelet 86.9±76.3, Lactate Dehydrogenase 393.5±176.1 U/L, Prothrombin time (PT) 17.1±8.8 x 10 9/L, Bilirubin 31.5±17.8, Aspartate Trans-Aminase (AST) 51.4±40.7 U/L, Alanine Aminotransferase (ALT) 52.9 ±47.5 U/L, urea 5.1 ±3.3 mmol/L, sodium (Na) 133.3 ±3.7mmol/L and Creatinine 86.0 ±30.2umol/L. Mean hospital stay was 6.3±2.8 days. Two ICU ad-missions (2.6%) were recorded. Mortality rate and cerebral malaria were 1.3% each. Hemolysis and hepatitis seen in 35.5% and 27.6% patients respectively. Malarial AKI were recorded in 13 patients (17.1 %) with KDIGO AKI stage 1(84.6%), stage 2 (7.7%) and stage 3 (7.7%). Among malarial AKI patients, one patient (7.7%) received dialysis, and twelve patients (92.3%) recovered renal function. Majority of laboratory features of malaria AKI showed proteinuria (100%), and hyperbilirubinemia (84.6%). Analysis of risk factors showed significant association of AST and male gender with malarial AKI. Conclusion: Malaria may lead to significant morbidity and mortality. Prompt management with volume replacement, antimalarial and dialysis brings about recovery of renal function in malarial AKI.